Defective mitophagy in aged macrophages promotes mitochondrial DNA cytosolic leakage to activate STING signaling during liver sterile inflammation. Issue 6 (22nd May 2022) - Zhong, Weizhe; Rao, Zhuqing; Xu, Jian; Sun, Yu; Hu, Haoran; Wang, Ping; Xia, Yongxiang; Pan, Xiongxiong; Tang, Weiwei; Chen, Ziyi; Zhou, Haoming; Wang, Xuehao
Abstract: Macrophage‐stimulator of interferon genes (STING) signaling mediated sterile inflammation has been implicated in various age‐related diseases. However, whether and how macrophage mitochondrial DNA (mtDNA) regulates STING signaling in aged macrophages remains largely unknown. We found that hypoxia‐reoxygenation (HR) induced STING activation in macrophages by triggering the release of macrophage mtDNA into the cytosol. Aging promoted the cytosolic leakage of macrophage mtDNA and enhanced STING activation, which was abrogated upon mtDNA depletion or cyclic GMP‐AMP Synthase (cGAS) inhibition. Aged macrophages exhibited increased mitochondrial injury with impaired mitophagy. Mechanistically, a decline in the PTEN‐induced kinase 1 (PINK1)/Parkin‐mediated polyubiquitination of mitochondria was observed in aged macrophages. Pink1 overexpression reversed the inhibition of mitochondrial ubiquitination but failed to promote mitolysosome formation in the aged macrophages. Meanwhile, aging impaired lysosomal biogenesis and function in macrophages by modulating the mTOR/transcription factor EB (TFEB) signaling pathway, which could be reversed by Torin‐1 treatment. Consequently, Pink1 overexpression in combination with Torin‐1 treatment restored mitophagic flux and inhibited mtDNA/cGAS/STING activation in aged macrophages. Moreover, besides HR‐induced metabolic stress, other types of oxidative and hepatotoxic stresses inhibited mitophagy and promoted the cytosolic release of mtDNA to activate STING signaling in aged macrophages. STING deficiency protected aged mice against diverse types of sterile inflammatory liver injuries. Our findings suggest that aging impairs mitophagic flux to facilitate the leakage of macrophage mtDNA into the cytosol and promotes STING activation, and thereby provides a novel potential therapeutic target for sterile inflammatory liver injury in aged patients. Abstract : Metabolic, oxidative stress and drug toxicity induced stress causes macrophage mitochondrial damage to promote cytosolic mtDNA release and STING activation. Mitophagy serves as an important negative feedback regulatory mechanism to mediate STING activation by degrading damaged mitochondia. Aging impairs mitophagy activation by inhibiting PINK1‐mediated mitochondrial ubiquitination and lysosome biogenesis and function.